Sequía, inmigración y políticas locales: el Sahel en la encrucijada del desarrollo - Nso, Sara (UNISCI Discussion Papers, 2007)
This article tries to identify the main socio-economic and political factors that relate desertification to international migration flows in the Sahel area. We study – not exhaustively, because of the lack of available data – those realities in Burkina Faso, Gambia, Guinea-Bissau, Guinea, Mali, Mauritania, Niger and Senegal, especially analysing the local element, without disregarding regional dynamics. From a “transnationalist” perspective, we will give the keys for a global understanding of the Sahel problems, with the aim of taking this region away from the crossroads of underdevelopment.